2019
DOI: 10.2478/popets-2019-0036
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Anonymized Bluetooth Devices

Abstract: Bluetooth Low Energy (BLE) devices use public (non-encrypted) advertising channels to announce their presence to other devices. To prevent tracking on these public channels, devices may use a periodically changing, randomized address instead of their permanent Media Access Control (MAC) address. In this work we show that many state-of-the-art devices which are implementing such anonymization measures are vulnerable to passive tracking that extends well beyond their address randomization cycles. We show that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 11 publications
0
28
0
4
Order By: Relevance
“…Contemporaneously and most closely related to our work, Becker et al [22] examine tracking devices using randomized BLE identifiers. While they examine OSes we do not (Windows, Android), their Apple evaluation considers the BLE messages to be largely uninterpretable data; we exhaustively reverse-engineer the Continuity protocol, revealing both the structure of the messages as well as what actions are required to produce them.…”
Section: Related Workmentioning
confidence: 95%
“…Contemporaneously and most closely related to our work, Becker et al [22] examine tracking devices using randomized BLE identifiers. While they examine OSes we do not (Windows, Android), their Apple evaluation considers the BLE messages to be largely uninterpretable data; we exhaustively reverse-engineer the Continuity protocol, revealing both the structure of the messages as well as what actions are required to produce them.…”
Section: Related Workmentioning
confidence: 95%
“…Cybersecurity vetting can take months, especially for newer products, which could prevent the rapid deployment of these technologies when they are most needed. The use of Bluetooth technology for exposure notification, for example, is far less invasive than the collection of WiFi or global-positioning-system location data, but Bluetooth is also known to be vulnerable to cyber attacks 39,40 .…”
Section: Privacy Concernsmentioning
confidence: 99%
“…One sensible hypothesis after analyzing the prior work on the security and privacy of wearables is that the increasing complexity of these devices and the functionalities they offer to their wearers, e.g., Bluetooth and Wi-Fi connectivity, increase the attack surface on the data that is collected, stored, and shared compared to on-board storing and processing in line with the general observation that "as the complexity of the environment increases, the number of elements in that environment creates additional risk" [47]. This, in turn, allows new points of entry for attackers that exploit Wi-Fi and/or Bluetooth vulnerabilities for such devices [11,60,67,74,90]. For example, security analysis of fitness tracking devices concluded that none could guarantee data integrity, authenticity, and confidentiality [30].…”
Section: Discussionmentioning
confidence: 93%
“…(1) MAC address disclosure can be partially prevented, according to expert E 1 , by (i) using address randomization whenever devices are broadcasting on public channels before the pairing phase and (ii) by using hash-or encryption-based anonymization; although see Demir et al [22] and Becker et al [11] for caveats, e.g., hash-based anonymization in Wi-Fi tracking systems can still be defeated by using an appropriate guesswork [22]. Since the glasses device acts as an Access Point, MAC address randomization could be implemented in several ways.…”
Section: Recommendations For More Secure Connected Camera Glassesmentioning
confidence: 99%
See 1 more Smart Citation